Spotted hyaena population density across habitat and land use types in southern Tanzania - Searle, CE; Strampelli, P; Smit, J; Mkuburo, L; Mathews, F; Kiwango, H; Macdonald, D; Loveridge, A; Dickman, A (Wiley, 2023)
Although the spotted hyaena (Crocuta crocuta) has been widely considered to be resilient to human disturbance, the species is now thought to be undergoing widespread population declines. Nevertheless, only a handful of population density estimates are available for the species, despite the importance of this information for informing conservation management. This is a consequence of both a lack of surveys and logistical challenges associated with processing spotted hyaena data. In this study, we collaborated with a cohort of students to process camera trap data from the Ruaha-Rungwa landscape initially collected to estimate lion (Panthera leo) and leopard (Panthera pardus) population density. By doing so, we provide the first spatially explicit population density estimates for spotted hyaena in Tanzania, via spatially explicit capture-recapture (SECR) modelling. We also examine the relationship between population densities of spotted hyaena, lion and leopard at each site. Spotted hyaena densities varied from 3.55 ± 0.72 adults and sub-adults per 100 km2 in a miombo (Brachystegia-Julbernardia) woodland area of Ruaha National Park, to 10.80 ± 1.08 per 100 km2 in a prey-rich open woodland savannah habitat in Ruaha National Park, with intermediate densities recorded in Rungwa Game Reserve and MBOMIPA Wildlife Management Area. Our results suggest that spotted hyaena density is influenced by prey availability and protection, and the species may be less resilient to human pressures than widely thought. Spotted hyaena densities were generally positively correlated with densities of lion and leopard, suggesting that prey availability and anthropogenic disturbance had a greater impact than interspecific effects in shaping large carnivore densities in this system. Overall, our study provides some of the first insights into an under-studied species in an under-researched part of its range, while shedding light into the impact of anthropogenic versus interspecific effects in shaping population status of spotted hyaena in human-impacted African systems.